The Study of Presentational and Discursive Symbol of Gawi Dance in Tenda Village, Ende Regency - Tina Mati, Reneldis; Jazuli, Muhammad; Utomo, Udi (Catharsis, 2019)
Gawi dance is a popular traditional dance in Ende Regency that has existed since the days of the Melehur and was inherited from generation to generation. Gawi dance is used in every traditional ceremony as an expression of gratitude and others as entertainment. The uniqueness of this dance lies in its shape resembling a snake circle (spiral), the rhythmic sound of the dancer's feet, and supported by musical accompaniment in the form of poetry from a solis without using text, properties such as machetes, tufted sticks tied to a horse's tail. The purpose of this study was to analyze the presentational and discursive symbols of the Gawi dance in the village of Tenda Regency in Ende. Qualitative research methods Interpretive with an interdisciplinary approach. Data collection techniques were observation, interview and document study. The data validity technique used source triangulation techniques. The data analysis technique used the theory of Susan K.Langer symbols with the stages of interactive model analysis. The results of the study suggested that Gawi dance has dance elements, namely motion, space and time, and supporting elements, namely accompaniment, clothing, makeup and property. The presentational symbol of Gawi dance could be seen in motion, space, accompaniment, clothing, makeup and property. The discursive symbol of Gawi dance was in the form of meanings such as religious meaning, unity, gender equality. The make-up of the Gawi dance means: valor and courage, beauty and neatness. The fashion of the Gawi dance has meaning: one's position, authority and pride. The implication of this research is that people can find out about the arts in the local area and increase the art treasury in Ende Regency.